1993
DOI: 10.1093/oxfordjournals.jbchem.a124146
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Phosphorylase Activity Associated with Platelet-Derived Endothelial Cell Growth Factor1

Abstract: Partial complementary DNA (cDNA) for thymidine phosphorylase (dThdPase) was cloned by means of a polymerase chain reaction. There was complete sequence identity between the amino acid sequence deduced from the nucleotide sequence of a clone (288 nucleotides) and the residues of platelet-derived endothelial cell growth factor (PD-ECGF). The amino acid sequence of all four peptide fragments from purified human dThdPase could be aligned with that of PD-ECGF. Our data indicate that residues 125-244 of PD-ECGF are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…In vivo, TFT is very dependent on TP activity, since adding TPI enhances bioavailability of TFT (Emura et al, 2005), which may favour the combination OHP-TFT, possibly leading to more DNA damage in cells and higher cytotoxicity. Secondly, TP is also known as PD-ECGF (Moghaddam and Bicknell, 1992;Sumizawa et al, 1993), which has stimulating properties on blood vessel formation in solid tumours (Takahashi et al, 1998). Previous studies showed that TPI inhibits blood vessel formation, thereby increasing apoptosis (Matsushita et al, 1999) and suppressing the formation of metastases (Takao et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, TFT is very dependent on TP activity, since adding TPI enhances bioavailability of TFT (Emura et al, 2005), which may favour the combination OHP-TFT, possibly leading to more DNA damage in cells and higher cytotoxicity. Secondly, TP is also known as PD-ECGF (Moghaddam and Bicknell, 1992;Sumizawa et al, 1993), which has stimulating properties on blood vessel formation in solid tumours (Takahashi et al, 1998). Previous studies showed that TPI inhibits blood vessel formation, thereby increasing apoptosis (Matsushita et al, 1999) and suppressing the formation of metastases (Takao et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is an angiogenic factor that was found to be chemotactic for endothelial cells in vitro and to induce neovascularization in several in vivo assays (Miyazono et al, 1987;Ishikawa et al, 1989;Sumizawa et al, 1993;Finnis et al, 1993). Studies have shown that TP expression was frequently elevated in human solid tumors, including colorectal cancers, where its expression was correlated with increased tumor microvessel density, increased tumor invasion and metastasis, and shorter patient survival time (Takebayashi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The angiogenic factor platelet-derived endothelial cell growth factor is identical to human thymidine phosphorylase (TP), an enzyme that catalyzes the reversible conversion of thymidine to thymine and 2-deoxyribose-1-phosphate; the latter is subsequently converted to 2-deoxyribose (2dR) (15)(16)(17)(18). TP is chemotactic for endothelial cells and has angiogenic activity in several in vivo assays, although it did not directly stimulate endothelial cell proliferation (16 -20).…”
mentioning
confidence: 99%